Modelling and Simulation of Complex Control Structures in Cell Biology - Sandblad, B.; Meinzer, H.P. (Methods of Information in Medicine, 1992)
Biological and biomedical tissues and organs represent very complex and highly dynamic systems. The problem to model such complex systems is twofold. First, it is necessary to identify and describe the biological properties and the connecting control mechanisms of the studied system and its subparts. Here, biological knowledge is often missing. Secondly, we are confronted with the problem to formulate the model of the control structure in a form that allows model analysis. Here, a normal mathematical formalism is often inadequate. To solve these modelling problems and to develop methods for building models of complex control structures that will enable the formulation of dynamic systems in biology, a framework for building such models is presented. The model framework is here mainly used for studies of dynamic cell structures, but the possible application areas are more general. An example is given for modelling cell structures of epithelial tissues in the intestine.
Keywords: Biological Models; Simulation; Control Structures; Cell Proliferation